Prediction of Quality of Life in Patients With Parkinson’s Disease With and Without Excessive Daytime Sleepiness: A Longitudinal Study - Zhang, Lixia; Chen, Yajing; Liang, Xiaoniu; Wang, Lan; Wang, Jian; Tang, Yilin; Zhu, Xiaodong (Frontiers in Aging Neuroscience, 2022)
Objective: There is a lack of longitudinal studies that directly compare quality of life (QoL) and investigate the impact of clinical factors on QoL across different excessive daytime sleepiness (EDS) statuses in Parkinson's Disease (PD); therefore, we aimed to compare QoL and reveal the potential heterogeneous predictors of QoL between PD patients with and without EDS. Methods: We collected clinical data among 306 PD patients over 2 years. EDS was assessed by the Epworth Sleepiness Scale and QoL was measured with the 39-item Parkinson's Disease Questionnaire. Results: We found that at both baseline and follow-up, PD patients with EDS had poorer QoL and suffered more non-motor symptoms including depression and clinical probable rapid eye movement sleep behaviour disorder (cpRBD). The generalized linear mixed model (GLMM) analysis indicated that the major predictors of QoL in PD with EDS were the akinetic-rigid type, disease duration and total levodopa equivalent dose, while in PD without EDS, the primary determinants of QoL were Hoehn and Yahr (H&Y stage), Mini-Mental State Examination (MMSE) and cpRBD. Conclusions: PD patients with EDS presented with poorer QoL. Besides, the baseline predictors of future QoL differed between PD patients with and without EDS. These findings remind clinicians to target specific clinical factors when attempting to improve QoL among PD patients.